2005
DOI: 10.1002/cyto.a.20123
|View full text |Cite
|
Sign up to set email alerts
|

SNP genotyping using microsphere‐linked PNA and flow cytometric detection

Abstract: Background: Single nucleotide polymorphisms (SNPs) represent the most frequent form of genetic variations. Some of the most sensitive methods for SNP genotyping employ synthetic oligonucleotides, such as the peptide nucleic acid (PNA). We introduce a new method combining allele-specific hybridization, PNA technology, and flow cytometric detection. We tested the design by genotyping a Danish basal cell carcinoma cohort of 80 individuals for an A/C SNP in exon 6 of the XPD gene. Methods: Genomic DNA was amplifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…However, amplification of genomic target DNA is a prerequisite to hybridization with conjugated probes in order to score discrete genotypes [Hadd et al, 2004;Rockenbauer et al, 2005]. Because amplification is inherently logarithmic and thus difficult to control, hybridization of these target sequences to conjugated oligonucleotide probes does not reproducibly and accurately quantify genomic copy number [Earley et al, 2002;Sekar et al, 2005;Vignali, 2000].…”
Section: Introductionmentioning
confidence: 99%
“…However, amplification of genomic target DNA is a prerequisite to hybridization with conjugated probes in order to score discrete genotypes [Hadd et al, 2004;Rockenbauer et al, 2005]. Because amplification is inherently logarithmic and thus difficult to control, hybridization of these target sequences to conjugated oligonucleotide probes does not reproducibly and accurately quantify genomic copy number [Earley et al, 2002;Sekar et al, 2005;Vignali, 2000].…”
Section: Introductionmentioning
confidence: 99%
“…Immunophenotyping is an important diagnostic tool for decision making in various diseases [1][2][3][4][5][6]. Typical examples are: -diagnosis of immunodeficiencies [7], -monitoring of systemic and chronic diseases [8][9][10][11][12], -cellular diagnostics of allergy [13,14], -functional characterization of cells [15,16], -genetic investigation [17,18], -differential diagnosis of lymphocytosis [19], -diagnosis of leukemia [5,[20][21][22][23][24], -investigation of T-cell receptor expression in Kawasaki syndrome [25][26], -investigation of pregnancy disturbances [27], -quality control in hemotherapy [28][29][30]. Furthermore, there are several indications that are presently not so important for routine diagnostics [31].…”
Section: Introductionmentioning
confidence: 99%
“…Rockenbauer et al reported a new method that combined allele-specific hybridization, PNA technology, and detection while using flow cytometry. These authors described a fully functional two-bead genotyping system based on PNA capture and flow cytometric detection that they used for the accurate and fast re-genotyping of a Danish basal cell carcinoma cohort [15]. Bethge et al synthesized forced intercalation probes (FIT-probes) that contained an intercalating cyanine dye, such as oxazole yellow (YO), which serves as a replacement for a canonical nucleobase.…”
Section: Introductionmentioning
confidence: 99%